2016
DOI: 10.1080/0284186x.2016.1230274
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular and perineural invasion in stage II rectal cancer: a report from the Swedish colorectal cancer registry

Abstract: Background: Adjuvant chemotherapy for stage II and III rectal cancer patients is a matter of discussion. The aim of the present study was to evaluate the prognostic value of lymphovascular (LVI) and perineural (PNI) invasion in stage II rectal cancer on a national level. Materials and methods: Clinico-pathological factors associated with disease-free survival (DFS) and time to recurrence in stage II rectal cancer patients were analyzed from patient data registered in the Swedish Colorectal Cancer Registry betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…In our study, LVI was identified as a significant predictor of recurrence. LVI was previously reported to be a predictor of recurrence in early-stage rectal cancer [26][27][28], which is consistent with our findings. LVI could be detected in the staging MRI with high specificity and moderate sensitivity [29,30] and could potentially be used to direct intensification of NACRT.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, LVI was identified as a significant predictor of recurrence. LVI was previously reported to be a predictor of recurrence in early-stage rectal cancer [26][27][28], which is consistent with our findings. LVI could be detected in the staging MRI with high specificity and moderate sensitivity [29,30] and could potentially be used to direct intensification of NACRT.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have identified several possible additional factors associated with recurrence. Patient factors, like intake of coffee and alcohol, smoking, weight-loss and Glascow Prognostic score [2] [3] [4] [5] [6], treatment factors like surgical experience and technique [7] [8], tumor factors like location, differentiation, vein-, nerve-and lymphatic ingrowth [9] [10] and molecular factors [11] [12] [13] [14] have been shown to influence cancer recurrence, and adjuvant oncological therapy is often recommended. In the present study, we have taken interest in what consequences repeated or aggravated inflammatory stress will inflict on the patient and influence the risk of recurrence after potential curative resection of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the developed nomogram incorporated a radiomics score derived from two components of the PET-based features, pN and LVI. Both are well-known clinicopathological prognostic factors in CRC patients [31][32][33]. Unexpectedly, AJCC stage was not identified as a significant factor in our multivariable COX proportional hazard model.…”
Section: Discussionmentioning
confidence: 64%